Ex Ante and Ex Post Discretion over Arm's Length Transfer Prices - Smith, Michael J. (The Accounting Review, 2002)
Treasury Regulations typically require a firm to use its manufacturing cost as one input in calculating the transfer price to be used for tax purposes. Because the characteristics of the firm's capital assets determine the realized manufacturing cost, the firm has an incentive to distort its investment choices in order to receive a more favorable tax transfer price. This represents an ex ante form of shifting income across divisions. Practical difficulties in enforcing the regulations provide the firm with another way to shift income. In particular, regulators often can identify only a range of acceptable transfer prices. As a result, the firm will not use the true “arm's length” transfer price, but will instead choose a transfer price that is more favorable for tax purposes. I find that the opportunity to shift income ex post in this manner may reduce the value of investment-based ex ante income shifting. That is, if the firm has more discretion over the ex post transfer price, then it may invest more efficiently ex ante. Although it is commonly perceived that ex post income shifting is purely deleterious, the analysis shows that it may have benefits.